MN typing discrepancies based on GYPA‐B‐A hybrid. Issue 4 (11th June 2014) - Polin, H.; Danzer, M.; Reiter, A.; Brisner, M.; Gaszner, W.; Weinberger, J.; Gabriel, C.
<x xml:space="preserve">Abstract</x> Background and Objectives Gene conversion events between GYPA and GYPB or GYPA and GYPE are facilitated by the close chromosomal proximity and high degree of sequence homology and can lead to the formation of GP hybrid genes. Discrepant results between blood group genotyping and haemagglutination in 22 random blood donors induced molecular characterization. Materials and Methods Sequence analysis of GYPA exons 1–7 and GYPB exons 1–5 was performed for gDNA and cDNA. The linkage of the nucleotide alterations was defined by haplotype separation. Results DNA analysis demonstrated a normal GYPA haplotype (GYPA*N n = 20, GYPA*M n = 2) with an altered GP hybrid nucleotide sequence in trans. A GYPB homologue sequence of minimal 10‐bp encompassing intron 1 and exon 2 was translated into GYPA, accounting for an amino acid substitution from arginine to glutamic acid at position 13 (38 C>A). Genomic DNA analysis demonstrated the cis‐linkage of the hybrid nucleotide sequence with each GYPA(Ser20, Gly24) (n = 20) associated with the expression of M and GYPA(Leu20, Glu24) (n = 2) encoding the N phenotype. The serologic data indicate that the changes do not affect the expression of a normal M and N antigen. cDNA sequences confirmed the gDNA results and furthermore identified a heterozygous deletion of GYPB exon 2 in all probands. Conclusion The results document a GYPA‐B‐A hybrid gene, probably produced via a single unequal homologous recombination event. A segmental transfer of GYPB seems most likely accounting for the allelic dropout.